Exportaç\~ao de bens primários e apreciaç\~ao do câmbio real: Há uma ligaç\~ao? - Nelson Marconi; Marcos Rocha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The real exchange rate (RER) can be considered one of the most important relative price of economics, given the influence it exerts on many other prices and variables, and may be overvalued, among other factors, as a symptom of the existence of a Dutch disease process. Thus, seeking to prove that assertion, this study investigated whether there is a relationship between the concentration of exports in commodities and appreciation of the real exchange rate. We constructed an index of RER misalignment from a cointegrated panel of 102 countries, in order to relate it to the type of export basket of countries. At first tests were undertaken to define the determinants of long-term real exchange rate and, subsequently, to identify those that contribute to its overvaluation. The results demonstrate that an export basket focused on primary products contributes to appreciate the real exchange rate, while an export basket with a higher share of manufactured products does not have the same effect, which is consistent with the effects expected by the theoretical models of Dutch disease.
Keywords: F10; F31; F32; F41; 330; real exchange rate; exports; Dutch disease